초등과학교육에서 차시대체형 STEAM 수업 개발 및 적용 - 채동현; 문병찬; 김은정; Chae, Dong-Hyun; Moon, Byoung-Chan; Kim, Eun-Jeong (대한지구과학교육학회지, 2014)
In this research, a subject substitute STEAM program was developed in context of a trend of STEAM education and a new science contents in a 2009 revised curriculum, which can replace the 2009 revised curriculum contents of 'Sound' unit in the third and the fourth grade. The developed program was taught to the 4th graders in a field. After applying the program, how students acknowledge the subject substitute STEAM program was analyzed through questionnaire. The research results were as follows. First, the subject substitute STEAM program of 3 sub programs was developed with centered around 'sound' unit for 4th graders. Second, students made a positive estimation of the STEAM program because of various activities and learning subject related to daily life. Third, they considered difficult term, necessary craft skills in creative design, understanding scientific principle and a lot of necessary time as difficulties of the STEAM program. And they also recognized that making stuff activity and learning aid material like activity sheet, picture and video helped to understand a lesson. Lastly, students had a positive thinking or negative thinking about STEAM program before they learn. But after learning the STEAM program, all of them showed their positive attitude to the STEAM program.